Transgenerational Succession’ Effects on Financial Performance of Listed Family Firms in the Arab Countries - Allioui, Azzeddine; Habba, Badr; Azizi, Taib Berrada El (European Scientific Journal, ESJ, 2020)
The purpose of this paper is to study the impact of succession events on the level and determinants of the financial performance of family businesses in the Arab world. This research is conducted through an empirical study on a sample of 166 family businesses in the Arab world. Firstly, the paper compares the financial performance of family businesses that continue to be managed by the founders with family businesses in which the management has been transferred to the successors. Secondly, this research identifies the determinants of the financial performance of the two categories through a multifactorial model based on the panel data method. The results revealed that succession negatively impacts the seizing of opportunities and growth in the market in the context of family businesses in the Arab region. Moreover, the paper clarifies the prudent policy that characterizes the transmitted family businesses, through the accumulation of resources and underinvestment. In this sense, this research provides evidence that family wealth and business affairs are interrelated in the tradition of clientelism, which is reflected in Arab countries by the transmission of family businesses to family successors. In other words, succession to inheritors is inevitable in the Arab context, and family businesses may show contradictory performances and stagnate, compared to first-generation family businesses.